Scribes and Schools in Monarchic Judah : a Socio-Archaeological Approach. - Jamieson-Drake, David W. (Library of Hebrew Bible/Old Testament studies., 1991)
The question of the existence and nature of scribal institutions in ancient Israel has up to now been debated primarily on literary grounds. In placing the question of scribes and schools in a socio-archaeological context, as the present study does, this problem is reformulated. The focus shifts from the question of the prevalence of literary skills to the broader question of the function of those skills within ancient society.